Status of Postpartum Intra Uterine Contraceptive Device in a Tertiary Care Hospital in Dhaka (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Timing of insertion, counseling, provider training and institutional support are critical factors for intrauterine contraceptive devices (IUCD) use during the postpartum period.Objective: The objective of the study was to determine the rate of acceptation, discontinuation, expulsion, infection and displacement of PPIUCD after vaginal delivery and cesarean section along with other complications among the study population.Methodology: This was a prospective observational study done in Shaheed Suhrawardy Medical College and Hospital from July 2015 to June 2016 among the pregnant women who delivered healthy baby by normal vaginal delivery and cesarean section. Data was collected by a structured questionnaire. Women who gave informed consent and who gave birth of healthy baby without complications were included. Women who had premature ruptured membrane with chorioamnionitis, pelvic inflammatory disease intrauterine fetal death or who did not give consent were excluded.Result: In this study, only 8.4% gave consent for this method, 77.1% had regular follow up after this method. Only 5.05% had removal and 1.8% had spontaneous expulsion. 10.5% had lower abdominal pain and 4.13% had per vaginal bleeding after this method.Conclusion: This study showed that post-partum intrauterine contraceptive devices insertion rate is low even in a tertiary center, which means, there is a lot of space for counseling the target population in our country. On the contrary, follow up rate was quite high which means that people are being concerned about this health care service. Similarly, the removal rate was also satisfying with minimum expulsion rate.Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 165-168